A Study on the Quality of Pork Sausages during Fermentation with Different Starter Cultures - Rao, Eswara; P.R.S., B. Moorthy; K., Sudhakara Reddy (Journal of Meat Science, 2012)
In this study, proximate composition, physico-chemical and microbiological characteristics were evaluated during fermentation and drying of pork sausages using different Lactic acid bacteria viz., Lactobacillus casei (LC), Lactobacillus plantarum (LP) and Pediococcus pentosaceus (PP). The per cent moisture of different meat sausages inoculated with lactic acid bacteria decreased significantly (P>0.01) whereas, per cent protein and fat increased during fermentation and drying. Among treatments, significantly (P>0.01) lower moisture and higher protein and fat content were observed in sausages treated with LP than PP and LC. Physico - chemical characteristics, pH, water holding capacity (WHC), water activity and cooking yield of pork sausages inoculated with Lactic acid bacteria were significantly (P>0.01) lower whereas emulsion stability and shrinkage were significantly higher than control after fermentation and drying. Among treatments significantly (P>0.01) lower pH, WHC, water activity and cooking yield and higher emulsion stability and shrinkage were observed in sausages treated with LP than PP and LC.The total plate count and yeast and mould count of pork sausages inoculated with different lactic acid bacteria, were significantly (P>0.01) higher whereas the Coliform count and the Salmonella count were significantly (P>0.01) lower than the control after fermentation. Significantly (P>0.01) higher total plate counts, yeast and mould counts and lower coliform and Salmonella counts were observed in sausages treated with LP followed by PP and LC during fermentation and drying process.
Keywords: Pork sausages; fermentation; starter cultures; drying